MENGIMPLENTASIKAN GERAKAN LITERASI SEKOLAH DI SDN PANTAI BAHAGIA 04 KECAMATAN MUARAGEMBONG - Hapsari Wijayanti, Sri; Setiyaningrum, Ari; Sihombing, Denny Jean Cross; Winson, Dimas Catur; Manurung, Lusya Anggraeny (LPPM Universitas Bina Bangsa, 2024)
The School Literacy Movement (GLS) is an Indonesian government program that fosters a liking for reading at all levels of education. In its implementation until now, many schools have not been able to implement it under the guidelines provided. SDN Pantai Bahagia 04 in Pantai Bahagia Village, Muaragembong District, Bekasi Regency, West Java, does not yet have a library. Teachers with their limitations have carried out reading activities for fifteen minutes of school textbooks before learning. This activity aims to promote literacy at SDN Pantai Bahagia 04 in Muaragembong sub-district, Bekasi district, by fulfilling the physical, social-affective, and academic environment aspects. A total of ten teachers were involved in the activity, which took place from June to August 2024. The method applied was GLS training and its implementation. The stages of this activity include training with tutorial, practice, and monitoring-evaluation. The knowledge test results on GLS showed that teachers' knowledge and understanding still needed improvement. However, in its implementation, teachers have practiced various reading techniques, created a classroom atmosphere with a literacy theme, and created fun activities after reading. Until now, the library has not been opened for students to read because data is still being finalized in the SLiMS and library administration. Nevertheless, the existing books can run GLS in their respective classrooms. Based on the conditions of students and schools, teachers understand the actual implementation of GLS. They are still in the process of realizing the physical, socio-affective, and academic environments